2023
DOI: 10.1002/mco2.216
|View full text |Cite
|
Sign up to set email alerts
|

Targeted therapy for pancreatic ductal adenocarcinoma: Mechanisms and clinical study

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is an aggressive and lethal malignancy with a high rate of recurrence and a dismal 5‐year survival rate. Contributing to the poor prognosis of PDAC is the lack of early detection, a complex network of signaling pathways and molecular mechanisms, a dense and desmoplastic stroma, and an immunosuppressive tumor microenvironment. A recent shift toward a neoadjuvant approach to treating PDAC has been sparked by the numerous benefits neoadjuvant therapy (NAT) has to offer comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 311 publications
(805 reference statements)
0
6
0
Order By: Relevance
“…Pi3K/AkT/mTOR signalling pathways in PDAC is often activated due to KRAS mutation leading to elevated cellular processes that help in growth, metabolism and survival [53]. This pathway is also involved in the initiation mechanisms of PDAC and inhibition of this is nowadays becoming popular with some therapies in preclinical and clinical trials [54]. Thus, effects of CFA on this axis can prove to be bene cial in terms of using CFA as treatment option for PDAC.…”
Section: Resultsmentioning
confidence: 99%
“…Pi3K/AkT/mTOR signalling pathways in PDAC is often activated due to KRAS mutation leading to elevated cellular processes that help in growth, metabolism and survival [53]. This pathway is also involved in the initiation mechanisms of PDAC and inhibition of this is nowadays becoming popular with some therapies in preclinical and clinical trials [54]. Thus, effects of CFA on this axis can prove to be bene cial in terms of using CFA as treatment option for PDAC.…”
Section: Resultsmentioning
confidence: 99%
“…However, it may be an alternative to surgery first for patients with clearly resectable disease who only have suspicious imaging findings of metastasis, CA 19-9 levels suggestive of metastatic disease, or who require medical optimization before surgery. Some studies support the use of NAT for treating resectable tumours[ 22 , 23 ], and others have shown that NAT may be considered for patients with resectable tumours and high-risk features[ 24 , 25 ]. A retrospective study aimed at exploring patient subgroups with high-risk resectable PDAC for selecting candidates who may benefit from NAT reported that NAT is an effective treatment for patients with resectable PDAC, particularly when the tumour is in contact with the portal vein/superior mesenteric vein and has a CA 19-9 concentration ≥ 150 U/mL[ 26 ].…”
Section: Current Treatment Trends In Natmentioning
confidence: 99%
“…Thus, nanotechnology-based localized immune activation may be more appropriate. In addition, tumor-led low antigenicity is another primary factor suppressing the immune response against PDAC, which needs to be amplified by locally activating immune-antigen presentation, increased antigen availability led T-cell and DC activation. , Even though PDAC is continuously transforming during its progression and becoming heterogeneous, it is extremely successful in remaining anti-immunogenic, which is a notable characteristic . This is mainly due to cell-based temporal signaling maintained throughout its transformation apart from suppressing spatial immunogenic stimuli .…”
Section: Nanotechnology-based Strategies To Enhance Immunotherapymentioning
confidence: 99%